Ekeland Variational Principle for Generalized Vector Equilibrium Problems with Equivalences and Applications - De-ning Qu; Cao-zong Cheng (Journal of Function Spaces and Applications)
The aim of this paper is to introduce Ekeland variational principle with variants for generalized vector equilibrium problems and to establish some existence results of solutions of generalized vector equilibrium problems with compact or noncompact domain as applications. Finally, some equivalent results of the established Ekeland variational principle are presented.